Islamic Economics as an Alternative Solution Amidst the Global Trade War - Awam Haikal; Kustin Hartini (Ushul Al-Hukm: Jurnal Syariah dan Hukum Islam, 2025)
This study aims to analyze Islamic economics as an alternative solution to address the instability arising from the global trade war. The research method uses a qualitative approach based on literature studies of secondary sources in the form of academic articles, international Islamic financial reports, and Islamic economic regulations. The results show that the principles of Islamic economics, especially the prohibition of usury (riba), gharar (gharar), and maysir (gambling), as well as the implementation of real asset-based transactions, can increase economic stability by reducing market speculation and strengthening the productive sector. Furthermore, the zakat mechanism and wealth distribution in Islamic economics have been shown to be effective in minimizing economic disparities and improving social welfare. These findings indicate that Islamic economics has the potential to be implemented as a more equitable, transparent, and sustainable global economic framework in conditions of uncertainty caused by the trade war.